Experiences of Sessional Educators within an Australian Undergraduate Paramedic Program - Williams, Brett; Beovich, Bronwyn (Journal of University Teaching and Learning Practice, 2017)
Background: The use of casual staff within the university undergraduate educational setting is a widespread phenomenon worldwide. However a lack of understanding exists regarding experiences of recruitment, support, professional development and other perceived professional needs in this area. Although previous studies of the experience of sessional educators have been reported in the literature, this is the first to describe experiences within the paramedic discipline.Objectives: To explore the experiences of sessional educators in an undergraduate program within the paramedic department of a university in Melbourne, Australia.Methods: A qualitative methodology was used that involved 10 semi-structured interviews with a purposive sample of sessional paramedic educators. Data collected from the interviews were thematically analysed to identify major issues from interview transcripts. The study was conducted in the paramedic department of a major university located in an outer metropolitan area of Melbourne, Australia.Results: Interview analysis identified five key themes of the sessional paramedic educator experience: informal processes, program inconsistencies, preparation for teaching, connection and support, and, educator benefits.Conclusion: This study fills a gap in the literature by describing the experiences of paramedic sessional educators, which was previously unreported. Many of the experiences expressed were commonly reported in the literature from other disciplines. Although the experiences was generally described as positive, the study identified a need for targeted support of these individuals, including formalisation of employment procedures, encouraging the open and timely transmission of information, as well as provisions for performance feedback and professional development.